2015
DOI: 10.1002/adma.201501803
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Enzyme‐Responsive Nanoparticles for Targeted Delivery and Accumulation in Tumors

Abstract: In this Communication, we describe an enzyme-responsive, paclitaxel-loaded nanoparticle and assess its safety and efficacy in vivo in a human fibrosarcoma murine xenograft. The material was generated via graft-through block copolymerization of norbornene monomers with hydrophilic targeting peptides together with hydrophobic paclitaxel prodrugs. This work represents a proof-of-concept study demonstrating the utility of enzyme-responsive nanoscale drug carriers capable of targeted accumulation and retention in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
179
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(184 citation statements)
references
References 58 publications
1
179
0
Order By: Relevance
“…Lastly, although we did not explore therapeutic molecule delivery here, it is important to note that the PPA system is amenable to the incorporation of a variety of therapeutics. In our hands, similar types of PPA particles have been prepared that contain small molecule drugs in the core, 18 or other peptides or nucleic acids in the shell. 20 Thus, this system can be easily modified for future therapeutic delivery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, although we did not explore therapeutic molecule delivery here, it is important to note that the PPA system is amenable to the incorporation of a variety of therapeutics. In our hands, similar types of PPA particles have been prepared that contain small molecule drugs in the core, 18 or other peptides or nucleic acids in the shell. 20 Thus, this system can be easily modified for future therapeutic delivery.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that this system initially designed for cancer diagnosis and treatment can also be applied to non-invasive NP delivery to ischemic myocardium. 13 Furthermore, the system is easily tunable and has been conjugated to a variety of imaging and therapeutic functionalities, 1820 providing proof of concept for minimally-invasive drug delivery and subsequent targeted retention. Our goal was to design enzyme-targeted PPA NPs and demonstrate their delivery and optimal biodistribution for targeting to ischemic muscle in a preclinical model of PAD.…”
Section: Introductionmentioning
confidence: 99%
“…300,200 A similar shapechanging system demonstrated active cargo release of bound drugs at the site of scaffold assembly in a fibrosarcoma tumor model. 76 These proof-of-concept works demonstrate exceptional utility achieved by the dynamic morphological response of enzyme-responsive micellar assemblies in two ways: first as a discrete vehicle for noninvasive intravenous delivery and second as a stationary scaffold for diagnostics and localized drug release.…”
Section: Structural Dynamics Of Polymer Assembliesmentioning
confidence: 98%
“…As such, considerable effort has been devoted toward the direct polymerization of complex peptides, 72 nucleobases, 73 bioderived polyesters, 74 imaging agents, 75 and therapeutic drugs. 76 These biosynthetic polymers possess extreme complexity with rigorous control over polymer assembly and in some cases biofunctionality as tumor targeting 77 and protease resistant materials. 78 In particular, protected and/or deprotected peptide-based monomers, which range in size from 5 to 30 amino acids, can be polymerized into dense brushes as homopolymers 79 or amphiphilic block copolymers that self-assemble into micellar nanoparticles.…”
Section: Architecture Controlmentioning
confidence: 99%
“…4,5 In particular, the ease with which these nanoparticles can be surface-functionalized 2 with a multitude of biologically active entities 2,6 has shown promise in many drug delivery applications. 5,7,8 Previously, we reported that ROMP-based doxorubicin-loaded PNPs can be modified with cationic surface moieties post-assembly to improve their stability in buffered media and in vitro cellular uptake. 7 However, the large diameters of these particles (~100–200 nm) may limit their cellular uptake 9 and tumor penetration when delivered in vivo .…”
mentioning
confidence: 99%